TERAPI NIMOTUZUMAB PADA PENDERITA GLIOMA PONTIN DEWASA - I NyomanDarsana, TiniKumara,I Gusti Ngurah Purna Putra (Neurona Majalah Kedokteran Neuro Sains, 2014)
A 37 YEARS OLD MALE REFERRED FROM JAYAPURA HOSPITAL TO THE EMERGENCY ROOM BECAUSE OF DECREASED OF CONCIOUSNESS ANDFEVER SINCE 7 DAYS BEFORE ADMISSION TWO WEEKS BEFORE HE HAD HISTORY OF SUDDEN SPINNING SENSATION AND FAINTED WHICH RESOLVED ON ONE DAY TREATMENT NEUROLOGIC EXAMINATION REVEALED GLASCOW COMA SCALE WAS 6 INTACT BRAINSTEM REFLEXES WITH RIGHT SPASTIC HEMIPARESIS AFTER SUPPORTING FLUID THERAPHY GCS IMPROVED INTO 11 NO FEVER BUT BULBAR PALSY WERE FOUND DYSFAGIA AND DYSPHONIA WITH DUPLEX SPASTIC HEMIPARESIS PATIENT WAS DIAGNOSEDAS PONTIN GLIOMA BASED ON CLINICAL FEATURES AND IMAGING BIOPSY PROCEDURE COULDNT BE DONE SO HE WAS PERFORMED RADIOTHERAPY AND CHEMOTHERAPY NIMOTUZUMAB IS A RECOMMENDED TARGETED THERAPY AND IT SHOWED A BETTER CLINICAL PROGRESS PATIENT CONTINUED GETTING NIMOTUZUMAB THERAPHY FOR 8 SERIES THEREAFTER HE SHOWED GOOD CLINICAL IMPROVEMENT WITH MINIMAL SIDE EFFECT AFTER 12 MONTHS OF FOLLOW UP